An Economic Evaluation of Emerging and Ineffective Interventions: Examining the Role of Cost When Translating Research into Practice. (April 2022) - Scheibel, Gretchen; Zane, Thomas L.; Zimmerman, Kathleen N.
Schools bear the burden of funding the majority of the services received by children with autism spectrum disorder (ASD) with the assumption that spent resources will result in meaningful positive outcomes for these students. Interventions lacking empirical support remain popular in schools despite lacking or limited evidence that students will experience positive outcomes. Economic evaluation methods provide a useful method of understanding the time and financial influences of these interventions. This study introduces a novel use of economic evaluation methods to examine the time and financial costs associated with two popular interventions lacking strong empirical evidence of effectiveness. The results of this study suggest that implementing either emerging interventions or those determined to be ineffective or harmful can pose a significant cost to schools with varying likelihood of benefit to children with ASD. Financial risk increases when implementing ineffective or harmful interventions in the form of opportunity cost. Implications and further application of these methods to research synthesis methods to better support educators selecting interventions is discussed.